ASSOCIATIONS BETWEEN SMOKING HABITS AND MAJOR ADVERSE CARDIOVASCULAR EVENTS IN PATIENTS WHO UNDERWENT CORONARY COMPUTED TOMOGRAPHY ANGIOGRAPHY. (April 2021) - Miura, Shin-Ichiro; Higashi, Sara; Yano, Masaya; Tashiro, Kohei; Idemoto, Yoshiaki; Suematsu, Yasunori; Shiga, Yuhei
Abstract: Objective: We analyzed that smoking could induce major adverse cardiovascular events (MACE) and the progression of coronary atherosclerosis as assessed by coronary computed tomography angiography (CCTA) as screening for coronary artery disease (CAD). Design and method: We enrolled 443 patients who had all underwent CCTA and either were clinically suspected of having CAD or had at least one cardiovascular risk factor. We divided the patients into smoking (past and current smoker) and non-smoking groups or males and females, and evaluated the presence of CAD and MACE (cardiovascular death, ischemic stroke, acute myocardial infarction and coronary revascularization) with a follow-up of up to 5 years. Results: %CAD in the smoking group was significantly higher than that in the non-smoking group. %MACE in males and smokers were significantly higher than those in females and non-smokers, respectively. Kaplan-Meier curves showed that smokers and females tended to show greater freedom from MACE than non-smokers and males, respectively (log-rank test p = 0.057 and p = 0.073, respectively). More interestingly, Kaplan-Meier curves also showed that non-smokers in females significantly greater freedom from MACE than smokers in females (p = 0.007), whereas there was no significant difference in freedom from MACE between non-smokers and smokers in males (p = 0.984). Although there were no significant predictors of MACE in all patients according to a multiple logistic regression analysis, smoking was useful for predicting MACE in females, but not males. Conclusions: Smoking was significantly associated with MACE in females, but not males, who underwent CCTA as screening for CAD. Various conventional risk factors may be associated with MACE in males.